Annual Plant Reviews Online 2020
DOI: 10.1002/9781119312994.apr0746
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cell‐wall Structure and Composition on Plant Freezing Tolerance

Abstract: Use policy The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 194 publications
(246 reference statements)
0
20
0
Order By: Relevance
“…The cell wall is the site of ice crystal formation during the freezing process, and the cell wall can prevent extracellular freezing damage to the plasma membrane (Panter et al, 2020 ). At the same time, it is well known that cell wall stress, along with turgor pressure, regulates cell expansion and growth (Cosgrove, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cell wall is the site of ice crystal formation during the freezing process, and the cell wall can prevent extracellular freezing damage to the plasma membrane (Panter et al, 2020 ). At the same time, it is well known that cell wall stress, along with turgor pressure, regulates cell expansion and growth (Cosgrove, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Across all 11 species studied, measurements of ε strongly suggest that hydrenchyma cell walls are highly elastic, and that this is responsible for their contribution to C FT . In addition, hemicelluloses, which are known to provide structural reinforcement to cell walls (Vanzin et al , 2002; Kim et al , 2020; Panter et al , 2020), were found at significantly lower abundances in the hydrenchyma in comparison to the chlorenchyma ( Fig. 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…2006 , Knight and Knight 2012 , Wisniewski et al. 2014 , 2020 , Panter et al. 2020 for comprehensive reviews).…”
Section: Introductionmentioning
confidence: 99%
“…During cold and sub-zero acclimation, the cell wall and extracellular space, referred to as the apoplast, experience significant remodeling that leads to the acquisition of freezing tolerance and avoidance ( Knight and Knight 2012 , Panter et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation